1992
DOI: 10.1111/j.1348-0421.1992.tb02109.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence Analysis of the Class G Tetracycline Resistance Determinant from Vibrio anguillarum

Abstract: The nucleotide sequence of the class G tetracycline resistance determinant previously isolated from Vibrio anguillarum has been determined. Two open reading frames of divergent polarity were identified. A resistance gene (tet A) encodes a protein of 393 amino acid residues (deduced molecular mass of 40.9 kDa), and a repressor gene (tet R) encodes a protein consisting of 210 amino acids with a calculated molecular mass of 23.6 kDa. Based on the deduced amino acid sequences, the proteins of tet A(G) and tet R(G)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…A floR homolog was first identified on a plasmid in Pasteurella piscicida recently renamed Photobacterium damselae, a fish pathogen [80]. In addition, the class G tetracycline resistance gene associated with the floR gene in the S. Typhimurium DT104 antibiotic resistance gene cluster was first identified in Vibrio anguillarum, also a fish pathogen [157]. The tet(G) gene has also been detected on plasmids of Photobacterium damselae [81].…”
Section: Origin Of the Sgi1 Antibiotic Resistance Gene Clustermentioning
confidence: 99%
“…A floR homolog was first identified on a plasmid in Pasteurella piscicida recently renamed Photobacterium damselae, a fish pathogen [80]. In addition, the class G tetracycline resistance gene associated with the floR gene in the S. Typhimurium DT104 antibiotic resistance gene cluster was first identified in Vibrio anguillarum, also a fish pathogen [157]. The tet(G) gene has also been detected on plasmids of Photobacterium damselae [81].…”
Section: Origin Of the Sgi1 Antibiotic Resistance Gene Clustermentioning
confidence: 99%
“…A floR homolog was first identified on a plasmid in Pasteurella piscicida recently renamed Photobacterium damselae, a fish pathogen [28]. In addition, the class G tetracycline resistance gene associated with the floR gene in the DT104 antibiotic resistance gene cluster was first identified in Vibrio anguillarum, also a fish pathogen [56]. The tet(G) gene has also been detected on plasmids of Photobacterium damselae [27].…”
Section: Chromosomal Antibiotic Resistance Gene Clustermentioning
confidence: 99%
“…Recent studies of the TnJO TetA protein have shown that it functions as a tetracycline/proton antiporter and that the species transported out of the cell is a divalent metal-tetracycline complex (57,60). Sequences for both tetA and tetR have been reported for class A (52), class B (tetA [19,34]; tetR [37]), class C (tetA [36]; tetR [46]), class D (tetA [2]; tetR [47]), and class G (62). For class E, the sequence of the tetR gene but not the tetA gene has been reported (45).…”
mentioning
confidence: 99%
“…family Enterobacteriaceae and related genera, resistance is most often due to a family of related tet genes (classes A through E and G), all of which mediate tetracycline efflux (26,27,29,62). The plasmids and transposons that define these six classes are RP1 and Tnl721 (class A), TnlO (class B), pSC101 and pBR322 (class C), RA1 and pIP173 (class D), pSL1456 (class E), and pJA8122 (class G).…”
mentioning
confidence: 99%